Estetika Motif Nyi Pohaci: Interpretasi Mitos Dewi Sri Dalam Desain Motif Kontemporer - Albahi, Haidarsyah Dwi; Budiono, Nadia Rachmaya Ningrum; Kemala, Alya Bela (Jurusan Seni Rupa ISBI Bandung, 2024)
This study aims to examine the Dewi Sri myth’s aesthetic value as a source of inspiration for digital creations featuring Nyi Pohaci motifs. The myth of Dewi Sri, the deity of fertility and rice in Indonesian agrarian culture, plays a significant role in illustrating the spiritual and cultural traditions of the society. This study employs a contemporary aesthetic methodology created by Prof. Dharsono. It is a multifaceted methodology that examines how form, colour, symbolism, emotions, and personal expression are all analyzed in this procedure of creating art. There are four stages to the study process for developing motif designs: 1) exploration, 2) experimentation, 3) contemplation, and 4) realization. This research also examines the socio-cultural context in which the myth of Dewi Sri was developed, resulting in an interaction between tradition and modernity in the creative process of labour. According to the research findings, Nyi Pohaci’s contemporary design has the potential to facilitate a dialogue between the past and the present, as well as to reflect aesthetic attractiveness. The design’s visual structure is intended to convey messages of harmony, balance, and fecundity about nature, which are pertinent to the current environmental and social issues.